A new species of shrimp of the genus Periclimenaeus Borradaile, 1915 (Decapoda: Caridea: Palaemonidae) from the southeastern Gulf of Mexico, including a key to the western Atlantic species of the genus - Ramos-Tafur, Gabriel E.; Lemaitre, Rafael (Zootaxa, 2017)
A new species of symbiotic palaemonid shrimp, Periclimenaeus mcmichaeli sp. nov., is described based on a single male specimen collected near Dry Tortugas, Florida, in the southeastern Gulf of Mexico. This new species, the 14th now known for the genus Periclimenaeus Borradaile 1915 from the western Atlantic, is morphologically most similar to P. wilsoni (Hay, 1917), from which it can be separated by the presence in the new species of two small subdistal teeth on the ventral margin of the rostrum, absence of small spinules or tubercles on ventral margin of the meri of the major and minor chelipeds, presence of three teeth on the cutting edge of the dactylus of the minor chela, and position of dorsal spines on the telson. The presence in this new species of a prominent acute projection on each pleurae of the third and fourth somite is documented, and appears to be a character previously overlooked in the taxonomic literature of species of the genus. This new species is compared with other similar congeners from the western Atlantic as well as other oceanic regions. An updated diagnosis for P. wilsoni, and a key to identify the western Atlantic species of the genus, are also presented.